Oncological safety of breast-conserving surgery after primary systemic chemotherapy in cT3–4 breast cancer patients - Jimbo, Kenjiro; Kinoshita, Takayuki; Asaga, Sota; Hojo, Takashi (Surgery today (Tokyo, Japan), 2015)
Purpose The aim of this study was to retrospectively assess the oncological safety of breast-conserving surgery (BCS) after primary systemic chemotherapy (PST) in terms of local recurrence (LR) in cT3–4 patients. Methods The subjects were 146 cT1–2 patients who underwent BCS after PST, and 169 patients with cT3–4 primary breast cancer. Of the 169 patients with cT3–4 disease, 20 underwent surgery first, and 149 underwent surgery after PST (mastectomy: 101 patients; BCS: 48 patients). The LR-free survival (LRFS) was analyzed using a Kaplan–Meier analysis. We evaluated the predictors using Cox proportional hazards modeling for LR after PST. Results There was no significant difference in 5-year LRFS between the cT1–2 and cT3–4 groups that underwent BCS after PST (98.6 vs. 92.5 %; P = 0.074). The 5-year LRFS was 94.7 % in the group that underwent initial surgery and 93.0 % in the PST group ( P = 0.845) in the cT3–4 patients, while the 5-year LRFS rates were 93.2 % in the BCS subgroup and 92.5 % in the mastectomy subgroup ( P = 0.958). In a multivariate analysis, the histological type, hormone negativity and a higher histological grade were independent predictors of LR after PST. Conclusions BCS after PST may be oncologically acceptable for cT3–4 breast cancers in terms of the LR compared with initial surgery or mastectomy after PST.